Determination of valproic acid dose level and influence of enzyme-inducing and non-enzyme-inducing drugs in volunteer patients of the city of Mérida, Venezuela - Cotuá Urzola, Juan Camilo (2017)
Objective: To determine valproic acid level/dose ratio (ND) and the influence of enzyme-inducing and non-enzymeinducing drugs in volunteer patients of the city of Mérida, Venezuela. Materials and methods: An experimental, observational, prospective, cross-sectional study was conducted at the Hospital de Mérida, Venezuela. After undergoing the inclusion and exclusion criteria process, patients signed an informed consent individually and voluntarily. The protocol consisted in collecting blood from 88 patients (42 males y 46 females) from 16 to 68 years old, who had partial or generalized seizures, and were receiving 3.97-38.04 mg/kg of valproic acid (AVP) twice a day as monotherapy or combination therapy with carbamazepine (CBZ), phenobarbital (PB), phenytoin (PHT), lamotrigine (LTG) and oxcarbazepine (OXC). A sample was taken after four weeks of treatment, in the fasting state and before the administration of the medication of the day. Afterwards, plasma concentration was determined through a radioimmunoassay method. The ND was established using the plasma concentration data. Results: AVP monotherapy showed a mean plasma concentration of 64.94 mg/l (SD 31.7) and ND of 4.32 (SD 2.1). Combination therapy with AVP+CBZ+PB showed an ND of 2.31 (SD 0.06), combination therapy with AVP+PB+PHT showed an ND of 2.46 (SD 0.43) and combination therapy with AVP+PB+OXC showed an ND of 4.63 (SD 3.12). Conclusions: The administration of concomitant drugs affected plasma concentration and AVP ND in a group of patients of the Hospital de Mérida, Venezuela.